DESKRIPSI DAN HABITAT MYCALESIS PERSEUS FABRICIUS, 1775 (RHOPALOCERA: NYMPHALIDAE) SPESIES KOSMOPOLITAN DI GUNUNG TOMPOTIKA, SULAWESI - Afrilianti, Cipta; Sataral, Mihwan; Elijonnahdi, Elijonnahdi; Fahri, Fahri (Univ. Tadulako, 2019)
This study aims to describe Mycalesis perseus Fabricius, 1775 and learn its habitat in Mt. Tompotika, Sulawesi. This research was conducted in February-March 2019. The butterflies was collected by using purposive sampling method with sweeping techniques using insect net along the hiking trails. The character of M. perseus is explained by the head, thorax, abdomen and wings. Mycalesis perseus characterized by ocellion the wing which borders with the white line on the postdiscal forewing and hindwing sections. Mycalesis perseus was found in secondary forest habitats and cashew gardens at an altitude of 100-200 meters above sea level.